Influence of agricultural wastes on shear strength properties of soil - Nik Daud, Nik Norsyahariati; Abdul Jalil, Falil Nisa; Sadiq, Muhammed Abubakar; Abd. Ghafar Azmi, Juliana (EDP Sciences, 2015)
Fiber reinforced soil is an effective and reliable technique for improving strength and stability of subgrade soil. Many studies have been conducted to investigate the influence of randomly distribution fiber inclusions in soil. Agricultural waste fiber was chosen as it is cheap, locally available, bio-degradable and eco-friendly. For this study, coir fiber and palm oil fiber will be implemented. Three types of soil with different properties were used to be mixed with both fibers. The present work will be focused on the influence of 1% waste materials into soils in terms of physical, chemical, morphological and mineralogical properties of waste-soil mixture and its relationship to the shear strength properties. Test result indicates that with addition of both fibers, the optimum moisture content (OMC) increased and the maximum dry density (MDD) decreased. Fibers inclusion can significantly decrease and increased the cohesion and internal angle of friction of soils, respectively.